TI_GERICHTE 72.2014.151 vom 30. Dezember 2014 , Rapina; lesioni semplici; minaccia. Scemata imputabilità di grado medio - TI Tribunale d'appello (2014)
Rapina; lesioni semplici; minaccia. Scemata imputabilità di grado medio